Pengaruh Pergantian Auditor, Ukuran Perusahaan, Dan Laba Rugi Terhadap Audit Report Lag Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia Periode 2022-2024 - Riani, Isabella Indah Permata; Nasywa, Sheva Alika; Muslim, Ade Imam (SM Institute, 2025)
Our current essay is focused on the industrial companies listed on the Indonesia Stock Exchange (IDX) for the years 2022–2024. We want to find out how Auditor Change (PA), Company Size (UKP), and Profit and Loss (LR) influence Audit Report Lag (ARL). Through the use of the Quantile Regression approach with Audit Opinion (OA), we can examine the relationship between Auditor Change (PA), Company Size (UKP), and Profit and Loss (LR) on Audit Report Lag (ARL). Findings from this article's analysis should shed light on the relative importance of auditor turnover, firm size, and profitability in explaining audit report lag for manufacturing companies listed on the IDX.